Identification and Analysis of Components in Yizhi Granule and Cynomolgus Monkey Plasma after Oral Administration by UPLC/ESI-Q-TOF MS and Their Protective Effects on PC12 Cells - Erwei Hao; Jianfeng Qin; Wei Wei; Jianhua Miao; Yan Xie; Xianglong Pan; Hangxuan Wu; Jinling Xie; Xiaosu Fan; Zhengcai Du; Xiaotao Hou; Jiagang Deng (Journal of Analytical Methods in Chemistry)
Yizhi Granule (YZG) is a health food containing six traditional Chinese medicines (TCMs). It improves memory barriers in rat experiments. Here, we describe the first fast and sensitive ultraperformance liquid chromatography/electrospray ionization quadrupole time-of-flight mass spectrometry (UPLC/ESI-Q-TOF MS) method for analyzing YZG in plasma. We used this technique for studies in cynomolgus monkey plasma. By comparing retention time, MS, and MS/MS data of reference compounds, 70 compounds were detected in YZG. Of these, 63 were identified including 60 saponins, 2 flavones, and 1 methyl ester. There were 33 saponins, 1 flavone, and 1 methyl ester in the plasma. Next, to study the therapeutic properties of YZG, the neuroprotective effect of some of the absorbed components was evaluated using PC12 cell damage caused by the Aβ25–35 model. The results showed that 9 compounds protect PC12 cells from Aβ25–35 with cell viability (%) of 111.00 ± 8.12 (G-Rb1), 102.20 ± 4.22 (G-Rb2), 100.34 ± 6.47 (G-Rd), 102.83 ± 2.10 (G-Re), 101.68 ± 7.64 (NG-Fa), 101.19 ± 7.83 (NG-R1), 102.53 ± 0.55 (NG-R2), 106.88 ± 4.95 (gypenoside A), and 103.95 ± 4.11 (gypenoside XLIX), respectively, versus the control group (87.51 ± 6.59). These results can reveal the real pharmacodynamic basis of YZG and provide a theoretical basis for subsequent studies. It can also provide some references for the research of Alzheimer’s disease.